THE RELATIONSHIP BETWEEN STUDENTS SATISFACTION IN LEARNING ACTIVITIES IN PICTURE STUDIO AND THE STUDENTS ACHIEVEMENT IN BUILDING PICTURE ENGINEERING SUBJECT AT SMK N 2 SIJUNJUNG - 847-866 , Afrimen Candra (CIVED, 2016)
ABSTRACTThe aim of this research to express the relationship between students satisfaction in learning activity in picture studio and  the students achievement in building picture engineering subject at SMK N 2 Sijunjung. The kind of this research is descriptive correlational. The population of this research were all of the students at twelve grade of Building Picture Engineering subject at SMK N 2 Sijunjung in academic years 2015/2016 the amount are 26 students. The sample of the research were all of the students at twelve grade of Building Picture Engineering subject at SMK N 2 Sijunjung, the research is  a population research. The primary data got from the questionnaire about students satisfaction in learning activities in picture studio, while the secondary data is the result of MID term test in stairs picture construction that got from the students. The technique of data analysis were: descriptive analysis, qualification test analysis, that consisted of test normality and test linearity for verify that data distribution from the sample that normal and linear distribution, and hypothesis test.The result of analysis showed that there is any low relationship and not significant between students satisfaction in learning activity in picture studio and  the students achievement in building picture engineering subject at SMK N 2 Sijunjung with the phase of faith 95%. It can be see from the value of Sig (2-tailed) 0,139 > Alpha (0,05). Based on the result of the test, it can be concluded that there is any relationship not significant between students satisfaction in learning activity in picture studio and  the students achievement in building picture engineering subject at SMK N 2 Sijunjung. Keywords: students satisfaction, picture studio, learning achievement